The postmodern paradox: freedom of expression and moral panic - Almiron, Núria (Estudios sobre el Mensaje Periodístico, 2026)
This essay argues that the restriction of freedom of expression in the name of protection against hate, polarization, or violence reflects a climate of moral panic that weakens democracy. The text first recalls that the defence of freedom of expression does not belong to any specific ideology, but rather forms part of an anti-authoritarian tradition aimed at limiting power. Second, it analyses how dominant identity-based approaches have contributed to delegitimizing this freedom through the gradual expansion (or concept creep) of notions such as harm, violence, and safety, as well as through a reductionist understanding of social conflict. Third, it critically examines the two main arguments used to justify new restrictions: that certain discourses cause violence and that limiting expression is a necessary evil to protect democracy. In response, the essay maintains that it is not possible to limit freedom of expression without eroding democracy, and that appeals to vague concepts such as “hate” essentially function as a social alarm mechanism that generates fear, discourages public criticism, and ultimately weakens democratic oversight of power—thereby increasing citizens’ vulnerability rather than protecting them.
Keywords: Freedom of Expression; Moral Panic; Hate Speech; Democracy; Censorship